2022
DOI: 10.1002/jcu.23186
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biliary stenting in endoscopic ultrasound‐guided tissue acquisition among patients with pancreatic cancer

Abstract: Introduction Pancreatic malignancies represent highly fatal diseases with poor prognosis and constantly increasing incidence despite modern diagnostic and therapeutic options. Both endoscopic ultrasound (EUS) and endoscopic retrograde cholangiopancreatography (ERCP) are regarded as mainstays in pancreatic cancer management. The present study aims to evaluate whether accuracy EUS with fine‐needle aspiration or biopsy (FNA or FNB) in pancreatic cancer diagnosis is influenced by prior biliary stenting or by techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Only four studies used strict criteria to define malignancy. 17 , 23 - 25 Tables 2 and 3 summarize the diagnostic outcomes for all studies based on the presence or absence of stents and stent type, respectively. 17 - 25 Supplementary Figure 1 presents the risk of bias assessment using the ROBINS-I tool.…”
Section: Resultsmentioning
confidence: 99%
“…Only four studies used strict criteria to define malignancy. 17 , 23 - 25 Tables 2 and 3 summarize the diagnostic outcomes for all studies based on the presence or absence of stents and stent type, respectively. 17 - 25 Supplementary Figure 1 presents the risk of bias assessment using the ROBINS-I tool.…”
Section: Resultsmentioning
confidence: 99%
“…From 91 studies identified using the search strategy, we included seven retrospective case-control studies [ 10 , 11 , 12 , 13 , 18 , 19 , 20 ] ( Figure 1 ) with 2458 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were conducted in Europe [ 10 , 11 , 18 , 20 ] and three in the USA [ 12 , 13 , 19 ]. Patients were recruited between periods ranging from 1998 to 2020.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Journal of Clinical Ultrasound: Sonography and other Imaging Techniques , an interesting original research article by Constantinescu et al 6 addresses the impact of biliary stenting in EUS‐TA in patients affected by pancreatic cancer, assessing and comparing the accuracy of sampling pancreatic malignant tissue by means of EUS‐TA in patients who underwent prior ERCP with biliary stenting and patients in whom ERCP was not performed. A total of 243 patients with pancreatic cancer who underwent ERCP and EUS‐TA, either with Fine‐Needle Aspiration (FNA) or Fine‐Needle Biopsy (FNB), were retrospectively evaluated.…”
mentioning
confidence: 99%